Making a Large Irrigation Scheme Work : A Case Study from Mali - Aw, Djibril; Diemer, Geert (Washington, DC: World Bank, 2012)
This report analyzes the government's decision on the outcome of a series of small power shifts triggered by pro-reform players. Reform advocates devised them whenever opportunities arose and used whatever maneuvering room there was to tilt the power balance between agency and farmers to further the goals of sustainability and partnership. The shifts were thought out for their strategic value, but most came without a timeline or plan for the next moves. Chapter 1 presents the Office du Niver (ON) scheme and its history. Chapters 2 through 5 analyze the reform process. Chapter 6 and appendix B discuss the parts that might be applied in other countries. Appendix A gives operational details on rightsizing the agency and the legal framework. Appendix C analyzes the political dimensions of irrigation reforms in other countries.